A novel role for gag as a cis-acting element regulating RNA structure, dimerization and packaging in HIV-1 lentiviral vectors. Issue 1 (20th December 2021) - Vamva, Eirini; Griffiths, Alex; Vink, Conrad A; Lever, Andrew M L; Kenyon, Julia C
Abstract: Clinical usage of lentiviral vectors is now established and increasing but remains constrained by vector titer with RNA packaging being a limiting factor. Lentiviral vector RNA is packaged through specific recognition of the packaging signal on the RNA by the viral structural protein Gag. We investigated structurally informed modifications of the 5′ leader and gag RNA sequences in which the extended packaging signal lies, to attempt to enhance the packaging process by facilitating vector RNA dimerization, a process closely linked to packaging. We used in-gel SHAPE to study the structures of these mutants in an attempt to derive structure-function correlations that could inform optimized vector RNA design. In-gel SHAPE of both dimeric and monomeric species of RNA revealed a previously unreported direct interaction between the U5 region of the HIV-1 leader and the downstream gag sequences. Our data suggest a structural equilibrium exists in the dimeric viral RNA between a metastable structure that includes a U5– gag interaction and a more stable structure with a U5–AUG duplex. Our data provide clarification for the previously unexplained requirement for the 5′ region of gag in enhancing genomic RNA packaging and provide a basis for design of optimized HIV-1 based vectors.